2020
DOI: 10.5194/hess-24-3627-2020
|View full text |Cite
|
Sign up to set email alerts
|

Investigating unproductive water losses from irrigated agricultural crops in the humid tropics through analyses of stable isotopes of water

Abstract: Abstract. Reliable information on water flow dynamics and water losses via irrigation on irrigated agricultural fields is important to improve water management strategies. We investigated the effect of season (wet season and dry season), irrigation management (flooded and non-flooded), and crop diversification (wet rice, dry rice, and maize) on soil water flow dynamics and water losses via evaporation during plant growth. Soil water was extracted and analysed for the stable isotopes of water (δ2H and δ18O). Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 87 publications
0
13
0
Order By: Relevance
“…Affected by precipitation infiltration and soil evaporation, the topsoil is often in the process of a dry wet alternation. Therefore, the parameter n in this paper takes the average value of 0.75, which represents the average dry‐wet condition of the soil (Mahindawansha et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Affected by precipitation infiltration and soil evaporation, the topsoil is often in the process of a dry wet alternation. Therefore, the parameter n in this paper takes the average value of 0.75, which represents the average dry‐wet condition of the soil (Mahindawansha et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…As an addition to the traditional ecological methods, the hydrogen and oxygen stable isotope technology has greatly improved the understanding of the water movement within the soil‐plant‐atmosphere continuum (Sprenger et al, 2016). The stable isotopes of hydrogen and oxygen in soil water can reveal precipitation, irrigation water infiltration process, soil water movement mechanism, soil evaporation, and so on (Deng et al, 2013; Goldsmith et al, 2012; Ji et al, 2021; Kleine et al, 2020; Mahindawansha et al, 2020; Yang et al, 2016; Zhao & Wang, 2018). Although the soil moisture regime under sand mulch has been highlighted in previous studies in arid land (Jiménez et al, 2005; Li, 2003; Sharma & Bhardwaj, 2017), the isotope‐based assessment is still limited, and the isotopic variability before and after irrigation was not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, providing water for crops consumes a large amount of water resources but also leads to a serious depletion of freshwater resources in China. Reducing the over-absorption of water by crops promotes a rise in the surface water table, which increases soil wetness and reduces the need for crop irrigation [40]. Thirdly, prolonged labour increases the morbidity rate of the agricultural workforce and even reduces the life expectancy of the workforce, thus lowering the quality and supply of labour.…”
Section: Research Hypothesismentioning
confidence: 99%
“…The macropore findings of the study by (Renée Brooks et al, 2010) have been confirmed to some extent in many biomes across the globe (Evaristo et al, 2016; Javaux et al, 2016). Other studies revealed that under a rainy temperate (Herve‐Fernandez et al, 2016), humid subtropical (Luo et al, 2019), tropical savanna (Mahindawansha et al, 2020) or subalpine (Langs et al, 2020) climate these interactions may be seasonally limited and dependent on soil moisture conditions. Bowling et al (2017) examined whether snowmelt water can create a unique pool of tightly bound water that is used by plants in seasonally snow‐covered areas during the growing season.…”
Section: Introductionmentioning
confidence: 99%